Metabolite Propile of Cassia occidentalis Leaves Extract Using Proton NMR (1H NMR) and LC-MS Molecular Network Analysis and its Antimicrobial Activity - Abdullahi Kobi, Zainab; Atiko, Rejoice; Ahmed Pantami, Hamza (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
The research focuses on profiling the metabolites in Cassia occidentalis leaves using 1H-NMR and LC-MS molecular network analysis, alongside evaluating its antimicrobial properties. The plant, known for its medicinal use in treating various diseases according to traditional herbalists, has been less explored using LC-MS molecular network analysis. The leaves were air-dried, extracted with methanol, and subjected to antibacterial activity test using various concentrations obtained from serial dilutions (200 mg/ml, 300 mg/ml, 400 mg/ml, 500 mg/ml and 600 mg/ml) and the test organisms was escherisha coli, salmonela specie, staphylococcus aureus, proteus, klebstella pneumoneae, shegella specie, pseudomonas, and entrobacter aerogenosa). The metabolite profile of Cassia occidentalis leaves extract was established by subjecting the sample to 1H-NMR analysis and LC-MS molecular network analysis. The antimicrobial tests demonstrated positive effects against all tested organisms at different concentrations. Proton NMR and LC-MS analyses revealed the presence of secondary metabolites, including apigenin, oleic acid, linolenic acid, lignoceric acid, 5, 7-dihydroxy flavone, mannitol, arachidic acid, leucine, valine, and alanine. This study adds literature information on C. occidentalis, emphasizing its antimicrobial properties and providing novel insights through LC-MS molecular network analysis.